Cracking investigation of a pressure transmitter tapping line. Issue 1 (16th May 2012) - Al‐Meshari, A.; van Zyl, G. N.; Diab, M.; Al‐Ghadeer, Y.
<x xml:space="preserve">Abstract</x> This article describes the findings of an investigation on cracking of ethylene furnace pressure transmitter tapping lines made of stainless steel type 304H. A detailed failure analysis using several characterisation techniques such as visual and metallographic examinations, SEM/EDX, XRF/C&S as well as finite element analysis uncovered that the cracking was caused by polythionic acid stress corrosion cracking that took place due to presence of condensate, sulphides and oxygen in contact with sensitised material. Several corrective measures to prevent similar failures are discussed.